Islam dan Budaya: Analisis Koleksi Peninggalan Masa Islam di Museum Sri Baduga Maharaja Bandung (1525-1900 Masehi) - Muhammad Aufa Rifqi; Muhammad Hilman Fitradinova; Muhammad Azka Adib Mukhtari; Heri Setiawan (Pusat Riset dan Inovasi Nasional, 2025)
This article examines the representation of Islamic culture through historical collections at the Sri Baduga Maharaja Museum in Bandung. It aims to analyze how artifacts such as momolo, Islamic glass paintings, and manuscripts like Serat Yusuf, Babad Banten, and Babad Cirebon reflect the process of Islamization and cultural acculturation in the Sundanese region from the 16th to early 20th century. This study employs historical methods with a qualitative approach, supported by interviews, direct observation, and literature review. The findings reveal that these collections not only hold historical value but also symbolic and educational significance, illustrating how Islamic values were integrated into local cultural frameworks in a peaceful and organic manner. Nevertheless, the curatorial interpretation of Islamic collections still requires improvement to better convey historical narratives and Islamic meanings in a contextual way to visitors.